2015
DOI: 10.4172/2324-8955.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Cerebrospinal Fluid and Plasma HIV-1 Envelope Sequences Isolated From a Single Donor with HIV Asymptomatic Neurocognitive Impairment

Abstract: Objective Combined antiretroviral treatment (cART) has changed the clinical presentation of HIV-associated neurocognitive disorders (HAND) to that of the milder forms of the disease. Asymptomatic neurocognitive impairment (ANI) is now more prevalent and is associated with increased morbidity and mortality risk in HIV-1–infected people. HIV-1 envelope (env) genetic heterogeneity has been detected within the central nervous system (CNS) of individuals with ANI. Changes within env determine co-receptor use, cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In a longitudinal study using autologous sequences from an ANI patient, we found a significant difference in the V4 net charge when comparing clones from plasma and CSF [25]. As in our previous study using plasma derived-clones, clones derived from the PBMCs of a subject with ANI also had an overall charge of −2.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In a longitudinal study using autologous sequences from an ANI patient, we found a significant difference in the V4 net charge when comparing clones from plasma and CSF [25]. As in our previous study using plasma derived-clones, clones derived from the PBMCs of a subject with ANI also had an overall charge of −2.…”
Section: Discussionmentioning
confidence: 66%
“…We sought to determine the genetic relationship among C2V4 sequences of isolates from subjects with or without HAND. We performed phylogenetic analysis of the C2V4 region of isolates, using MEGA 6.0 with default penalties [25]. Figure 1 shows the resulting neighbor-joining phylogenetic tree of the 73 C2V4 env sequences from clinical isolates and 5 reference env sequences used as outgroup controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A classic clinical study found that HIV-1 sequences from CSF were more genetically diverse within the C2V3 region of HIV + subjects with severe neurocognitive impairment than they were in those same regions of HIV + subjects without cognitive impairment (45). However, other studies show that the autologous genetic diversity within V3 in CSF env s is usually lower than plasma env genetic diversity (46, 47). …”
Section: The Role Of the Hiv-1 Envelope In Cns Infectionmentioning
confidence: 93%